Case study of SABIC: Saudi company producing petrochemicals for global market needs - Mohd Israil, Khaliq Ahmad; Bulbul, Afroza (International Open University Press, 2025)
SABIC is a big company with several affiliates. The company recorded a net profit of US$ 5.7 billion in 2018. The company, SABIC (Saudi Basic Industries Corporation) was founded back in 1976 by a royal decree to develop the country specializing in by-products of oil extraction for the value-added commodities such as chemicals, polymers and fertilizers including the high-performance plastics, agro-nutrients, and metals. The company’s export markets are the Americas, Europe, Middle East, and the Asia Pacific. The business interest indirectly supports customers in construction, medical devices, packaging, agro-nutrients, electrical and electronics, transportation and is a source of clean energy for international clients. Beside a net profit of US$ 5.7 billion, SABIC sales revenues for 2018 totaled US$ 45 billion. Its total assets stood at US$ 85 billion in same corresponding year. Production capacity was 75.3 million metric tons during 2018. SABIC is source of bread and butter for more than 33,000 employees worldwide and operates in around 50 countries. The Saudi Arabian government owns 70 percent of SABIC shares with the remaining 30 percent publicly traded on the Saudi stock exchange. On another note, Islam is a comprehensive and all-inclusive religion that integrates with Muslims’ life at all levels and covers every single aspect of not just a Muslims’ relationship with Allah but mundane life as some might think otherwise. The religion for Muslims governs and regulates daily life from within in terms of beliefs (Aqidah) and actions (Sharia) as well as business ethics and morals (Akhlaq) as part of it. SABIC affiliated companies are SABIC Sukuk, Saudi Iron & Steel Company (Hadeed), National Industrial Gases Co (Gas), etc. Even companies such as Saudi Methanol Co (Ar-Razi), Korea Nexlene Company (KNC), etc. are its associates. Islam is an official religion of the Kingdom and business environment for all companies are obligatory for Muslims by the Saudi laws, of fasting in Ramadhan, performing Hajj and having prayer area and halting the work for 10 minutes during each prayer for five times daily is established culture for any businesses to operate. Ablution (Wudu/daily wash) facilities for Muslims to perform prayers as a religious obligation is must even in the headquarters for SABIC in Riyadh/Jubail. As SABIC management undertake a guardian leadership style as a suitable choice for a just and fair workforce motivation and guarantees ROI for the shareholders.